Internal Offloading or Surgical Offloading Adjuvant Techniques in the Reconstruction of Diabetic Plantar First Metatarsal Head Ulcer For Lasting Results - Thalaivirithan Margabandu Balakrishnan; Srividya Madhurbootheswaran; Vanya Butcha; Anjana Elangovan; J. Jaganmohan (Indian Journal of Plastic Surgery)
Introduction Management of diabetic foot ulcers (DFUs) is subverted by recurrences. The main cause for the recurrence of DFUs is the failure to recognize and address all the faulty biomechanics precipitating and perpetuating the ulcer. So, we have devised a protocol for treating the diabetic plantar first metatarsal head ulcer (DPFMHUs) incorporating structured internal offloading procedures in conjunction with reconstruction. Aim The aim of this study was to evaluate our protocol in the management of DPFMHUs. Materials and Methods Fifty-one patients (31 males and 20 females) with DPFMHUs were managed with our protocol in this prospective cohort study conducted from March 2015 to March 2020. All the faulty biomechanics were addressed by tailored internal offloading procedure as per the protocol. Results All patients were followed up for an average period of 23.7 months. Early complications were in the form of wound infection (3 patients, 5.9%) and seroma/hematoma (2 patients, 3.9%). Late complication in the form of recurrence was seen only in one patient (1.9%); rest of the patients had no recurrence (98%). Transfer lesions were noted in six patients (11.8%). Conclusion Our tailored protocol, which addresses all the faulty biomechanics associated with the DPFMHU, may be very helpful in preventing the recurrence and to give lasting results. It is imperative to design a tailored internal/surgical offloading procedure for all deforming forces that are responsible for precipitation and perpetuation of DPFMHUs, in addition to like tissue reconstruction.